2002
DOI: 10.1053/jhep.2002.36130
|View full text |Cite
|
Sign up to set email alerts
|

Albumin dialysis in cirrhosis with superimposed acute liver injury: A prospective, controlled study

Abstract: Patients with liver cirrhosis and a superimposed acute injury with progressive hyperbilirubinemia have a high mortality. A prospective, controlled study was performed to test whether hyperbilirubinemia, 30-day survival, and encephalopathy would be improved by extracorporeal albumin dialysis (ECAD). Twenty-four patients were studied; 23 patients had cirrhosis; 1 had a prolonged cholestatic drug reaction and was excluded from per protocol (PP) analysis. Patients had a plasma bilirubin greater than 20 mg/dL and h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

11
223
2
23

Year Published

2003
2003
2015
2015

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 376 publications
(259 citation statements)
references
References 23 publications
11
223
2
23
Order By: Relevance
“…4,[10][11][12] Current hypotheses suggest that the removal of excess protein-bound toxins in the extracorporeal circuit is likely to regenerate the native albumin, thereby enhancing its functional capacity so that it may be able to transport and detoxify more toxins. Contrary to this existing hypothesis, albumin dialysis using MARS did not improve the measured functional capacity of the patient's circulating albumin.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…4,[10][11][12] Current hypotheses suggest that the removal of excess protein-bound toxins in the extracorporeal circuit is likely to regenerate the native albumin, thereby enhancing its functional capacity so that it may be able to transport and detoxify more toxins. Contrary to this existing hypothesis, albumin dialysis using MARS did not improve the measured functional capacity of the patient's circulating albumin.…”
Section: Discussionmentioning
confidence: 99%
“…One such device that is commercially available is the Molecular Adsorbents Recirculating System (MARS) (Gambro, Lund, Sweden) and studies using this device show beneficial pathophysiological and clinical effects particularly in reducing the severity of hepatic encephalopathy with small studies also showing possible survival benefit in liver failure patients. [10][11][12] However, at present, detailed functional characteristics of the different binding sites in cirrhosis have not been determined. The overall aim of this study was to perform a detailed qualitative and quantitative assessment of the functional capacity of albumin in patients with liver disease of varying severities and to determine whether these alterations could be used as a marker of disease severity and prognosis.…”
mentioning
confidence: 99%
“…52 Of note, the presence of renal failure requiring dialysis was specifically excluded in this study. Because the investigators used the trend of bilirubin (which is outcome specific in alcoholic hepatitis only) as a "surrogate marker," the study also excluded patients who responded to conventional therapy, indicated by a spontaneous decrease of bilirubin, implementing a 3-5 days long "pre-phase" prior to enrollment.…”
Section: ©2 0 1 1 L a N D E S B I O S C I E N C E D O N O T D I S Tmentioning
confidence: 99%
“…7,8 In addition, improved outcome has been demonstrated in patients with hepatorenal syndrome and acute-on-chronic liver failure. 9, 10 The aim of this study was to assess the safety, efficacy, and feasibility of MARS treatment in patients with EAD after OLT.…”
mentioning
confidence: 99%